Conspiracy beliefs and pandemic related behaviours: a study from India - Dubey, Chahat; Hameed, Noufal T.; Satheesan, Sisira C. (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 pandemic is still affecting large sections of populations all over the world. Thousands of deaths and damages to life that are indescribable, the pandemic has not yet come under control. Several studies show a significant impact of the same on mental health. The present study aimed at understanding conspiracy beliefs and pandemic related behaviors. It also aimed at documenting the level of distress reported. Methods: The cross-sectional quantitative study was conducted among the public from India. The study assessed conspiracy beliefs, pandemic related behaviors, and psychological distress using standardized questionnaires. Basic demographic details were also collected. The questionnaires were converted to Google form, and the link was sent to the public along with a description of the study. Quantitative analysis was used, including frequency, mean, standard deviation, and student t-test. Results: Hundred and thirty individuals (49 males and 81 females) participated in the study (mean age=29 years). About half of the participants reported higher levels of distress. No significant gender difference was found on the endorsement of conspiracy beliefs or in engagement in pandemic related behaviors. Engagement in pandemic related behaviors was significantly higher among participants who reported high levels of distress. However, on the endorsement level of conspiracy beliefs, there was no significant difference between those who reported high or low levels of distress. Conclusions: Endorsement of conspiracy beliefs, engagement in pandemic related behaviors, and psychological distress are important variables that require attention at the present scenario.